2011
DOI: 10.1007/s12599-011-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Willingness to Use Mobile Location-Based Services

Abstract: Mobile network operators regard mobile location based services as a services category promising considerable business volume. However, up to now, the expectations were not met in full. The questions arise, what the reasons for demand restraint are, and how it can be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…having it all in one place on an app would be ideal.'' This view seems in line with the findings from previous studies suggesting that the relative advantage of convenience and saving time are important benefits to those looking to adopt a mobile app (Gerpott & Berg, 2011;Hu, Li, & Hu, 2008).…”
Section: Targeted Mobile App Benefitssupporting
confidence: 90%
See 2 more Smart Citations
“…having it all in one place on an app would be ideal.'' This view seems in line with the findings from previous studies suggesting that the relative advantage of convenience and saving time are important benefits to those looking to adopt a mobile app (Gerpott & Berg, 2011;Hu, Li, & Hu, 2008).…”
Section: Targeted Mobile App Benefitssupporting
confidence: 90%
“…While some of these findings were unique to this marine context (i.e., compatibility with boaters' values through environmental education opportunities), many were in line with previous research including the importance of incorporating useful features lacking in current technology (Rogers, 2003;Verkasalo et al, 2010) and that the innovation saves the user time (Gerpott & Berg, 2011;Hu et al, 2008) at a relatively low cost (Hu et al, 2008;Rogers, 2003). These theoretical ties are worthy of consideration in campaign planning and implementation as they suggest a structure for systematic consideration of influential factors for increasing and directing the target audience's mobile app adoption likelihood.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, numerous studies have found that privacy concerns and privacy risk perceptions positively affect consumers' lurking behavior and selfconcealment [51]. Privacy risk perceptions also negatively affect consumers' willingness to provide personal information [15], [28], [39] and to use online services [20], [21], [68], [69], thereby eventually leading to losses for online businesses [60] and exerting a considerable negative effect on online business performance [59]. Thus, because of the increasing importance of e-marketing and growing concerns regarding online privacy protection [6], the role of privacy risk in e-marketing is more crucial than ever before.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have explored the role of product characteristics such as perceived benefits of service use [10], [16] and compatibility [21] in privacy risk perceptions. Other studies have observed the effects of social influence [20], trust in service providers [20], [39], [50], [63], [68], [69], perceived justice [70], perceived exchange fairness [41], and perceived control [39] on perceived privacy risk.…”
Section: Introductionmentioning
confidence: 99%